Digital image processing with C++ implementing reference algorithms with the CImg library - Tschumperle, David; Tilmant, Christophe; Barra, Vincent (CRC Press, 2023)
"Digital Image Processing with C++ presents the theory of digital image processing, and implementations of algorithms using a dedicated library. Processing a digital image means transforming its content (denoising, stylizing, etc.), or extracting information to solve a given problem (object recognition, measurement, motion estimation, etc.). This book presents the mathematical theories underlying digital image processing, as well as their practical implementation through examples of algorithms implemented in the C++ language, using the free and easy-to-use CImg library. Chapters cover in a broad way the field of digital image processing and proposes practical and functional implementations of each method theoretically described. The main topics covered include filtering in spatial and frequency domains, mathematical morphology, feature extraction and applications to segmentation, motion estimation, multispectral image processing and 3D visualization. Students or developers wishing to discover or specialize in this discipline, teachers and researchers wishing to quickly prototype new algorithms, or develop courses, will all find in this book material to discover image processing or deepen their knowledge in this field"--
Includes bibliographical references (pages 285-288) and index. - Description based on online resource; title from digital title page (viewed on March 31, 2023)
Keywords: Image processing -- Digital techniques -- Computer programs; Libraries (Computer program subroutines); C++ (Computer program language); Traitement d'images; Techniques numériques; Logiciels; C++ (Langage de programmation); COMPUTERS / Computer Graphics / Image Processing (see also PHOTOGRAPHY / Techniques / Digital); COMPUTERS / Programming Languages / C++; COMPUTERS / Programming / Algorithms; Image processing; Digital techniques; Computer programs